2013
DOI: 10.1080/15378020.2013.850382
|View full text |Cite
|
Sign up to set email alerts
|

The Usefulness of the Theory of Planned Behavior: Understanding U.S. Fast Food Consumption of Generation Y Chinese Consumers

Abstract: The purpose of this study was to assess how well a popular U.S. developed behavioral model, the theory of planned behavior, was able to explain Generation Y Chinese consumers' purchase behavior regarding a fast food restaurant meal. Results provided considerable support in terms of robustness of the theory of planned behavior to predict and explain intentions to buy a fast food meal. The model also provided reasonable measures of fit for the Chinese sample. The findings can enhance the extant literature on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 43 publications
2
12
0
2
Order By: Relevance
“…It could be argued that a complete study of international students' psychological variables related to acculturation experiences should follow a model that includes all of these aspects, but, of course, then it would be difficult to do research on these issues with the limited funding that most tourism researchers usually have. However, the overall finding of this thesis support the claims by (Padgett et al, 2013;Tartakovsky, 2012;Wu & Mak, 2011) that experiences and individuals' characteristics are among the variables that could further explain intentions or in this thesis specifically, destination-loyalty intention in international education.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…It could be argued that a complete study of international students' psychological variables related to acculturation experiences should follow a model that includes all of these aspects, but, of course, then it would be difficult to do research on these issues with the limited funding that most tourism researchers usually have. However, the overall finding of this thesis support the claims by (Padgett et al, 2013;Tartakovsky, 2012;Wu & Mak, 2011) that experiences and individuals' characteristics are among the variables that could further explain intentions or in this thesis specifically, destination-loyalty intention in international education.…”
Section: Discussionsupporting
confidence: 81%
“…Empirical evidence has shown that acculturation is a process relevant to loyalty intentions Padgett, Kim, Goh, & Huffman, 2013;Tartakovsky, 2012;Wu & Mak, 2011). To further understand the acculturationintention relationship, this thesis is based on the contributions of John Berry and his colleagues .…”
Section: Framework and Perspectivementioning
confidence: 99%
“…This is considered surprising in view of the multigenerational nature of visitors and workforce that span the entire industry (Kapoor & Solomon, 2011;Barron, Leask & Fyall, 2014) and the fact that demographic change is, arguably, the strongest force for change over the next generation (McRae, 1995;von Bergner & Lohmann, 2013). Interestingly, this is despite more generic studies on workforce characteristics ; leadership (Stanat, 2005;Hagermann & Stroop, 2013); the consumption of fast food (Padgett, 2009); sports consumption (Johnson, Summers & Jocumsen, 2006); and fashion (O'Cass & Choy, 2008). More specifically, the paucity of studies on Gen Y in the visitor attraction sector is surprising as it represents a sector where all generations visit and work together, as evidenced by studies conducted by Leask, Fyall and Barron (2013a;2013b) among others (see Prideaux, Yee-Sum Lee & Tsang, 2016).…”
Section: Introductionmentioning
confidence: 74%
“…Penelitian ini menggunakan teori yang sama untuk perilaku menabung di program PKK. Teori tersebut melibatkan variabel-variabel yang mudah dioperasionalkan dan telah digunakan secara luas di berbagai studi perilaku seperti perilaku penggunaan Mcommerce (Mishra, 2014); minat beli (Padgett, Kim, Goh, & Huffman, 2013;Wang, 2014); dan perilaku hidup sehat (Jiang, Lu, Hou, & Yue, 2013) Beranjak dari relasi variabel-variabel yang terdapat dalam TPB maka tujuan studi ini adalah untuk menguji: (a) pengaruh sikap, norma subjektif, dan kontrol perilaku persepsian terhadap minat untuk menabung di PKK dan (b) pengaruh minat untuk menabung terhadap perilaku menabung rumah tangga di PKK. Adapun kontribusi dari studi ini adalah memberikan referensi studi perilaku menabung rumah tangga di PKK yang selama ini belum menjadi perhatian untuk diteliti dan memperluas penerapan TPB di bidang keuangan rumah tangga.…”
Section: Pendahuluanunclassified